The effects of acute static stretching on reaction time and force - Alpkaya, U.; Koceja, D. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The purpose of this study was to determine alterations in explosive force production and reaction time following the soleus and gastrocnemius muscle stretching. Specifically we investigated whether or not actually stretching the calf muscles would alter the performance of reaction time and force production. Methods: Fifteen subjects (age: 25.07±5.35 years; height: 1.76±0.07 m; weight: 81.38±17.28 kg) completed 2 test sessions. All subjects underwent a warm-up of 5 min bicycling and stretching of the ankle plantar flexors followed by reaction time and force tasks, and a similar control period of no stretch of the ankle plantar flexors. Measure of reaction time and force were assessed following stretching and no stretching conditions. Results: There were no significant differences in reaction time and force between the stretching and control conditions (P>0.05). Conclusion: These results demonstrated that 3 sets of 15 s duration of the static stretching did not have a positive or negative effect on reaction time and explosive force.